The methods of estimation of reliability of light warning systems of aerodromes - Зеленков, И. А.; Ососкова, Т. И. (Proceedings of National Aviation University (archive), 1998)
Considered here are the criteria of reliability: indicators of non-failure operation and complex indicators of reliability. The considered indicators allow us to make a comparative estimation of the quality of the work of the system and to make approximate estimation of their economic efficiency. The estimation of reliability of the light warning system of aerodromes was carried out by means of comparison of the rated indication and the norms given by ICAO